ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMATIAN IBU AKIBAT PRE EKLAMSI/EKLAMSI DI RSUD INDRAMAYU TAHUN 2013 - Yulaikhah, Lily; Stia Murni, Dewi Eka; Putri, Nanda Yansih (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
High maternal mortality rate in Indonesia is largely caused by the classic triad of causes of maternal deaths are haemorrhage, eclampsia and infections. Conditions in Indramayu the number of maternal deaths 44 in 2012 and 46 the mother in 2013 turned out most of it is caused by pre eclampsia / eclampsia is a number of 21 people (47.73%) in 2012 and there is an increase to 24 people (52.17% ) in 2013, with data show that the number of deaths with number 13 (54.17%). This study aims to determine the factors associated with maternal mortality due to pre-eclampsia / eclampsia seen from maternal factors, socio-economic, medical history and condition of pregnancy, age, parity, nutrition, medical history, socioeconomic, and so forth. The study was conducted by using the analytical method retrospective cross-sectional design, then performed statistical analysis using univariate, bivariate and multivariate. The population is all pregnant women with pre-eclampsia / eclampsia were treated in hospitals Indramayu in 2013 some 254 people. Results of univariate analysis in this study showed that based on genetic factors number of pregnant women with pre-eclampsia is largely a history of severe disease, no history of pre-eclampsia in a previous pregnancy, and do not have a history of pre-eclampsia in the family. while based on biological factors the number of pregnant women with pre-eclampsia in the range of 20-35 years of age, with parity multiparous, single pregnancies and did not experience molahidatidosa and polyhydramnios. While it is based on behavioral factors, the number of pregnant women with pre-eclampsia mostly low educational background and not bekerja. Conclusion this study that there is a relationship between risk factors in maternal mortality due to pre-eclampsia / eclampsia is pregnancy. whereas other risk factors no significant association with the incidence of maternal deaths due to pre-eclampsia / eclampsia. Thus the need to look for other risk factors associated with maternal mortality due to pre-eclampsia / eclampsia. Keywords: Pre Eclampsia/Eclampsia, Death, Mother, Risk Factor